Triage Approaches Send Adverse Political Signals for Conservation - Buckley, Ralf C. (Frontiers in Ecology and Evolution, 2016)
Conservation can be analysed as a political game between advocates and opponents, and games include signals. Triage approaches aim to trade off conservation gains and losses for different ecosystems, species, sites and subpopulations, in an attempt to reduce aggregate net losses. These approaches send a political signal that some local or global species extinctions are socially acceptable. This permits conservation opponents to argue that any species may become extinct where convenient to development interests. Endorsement of triage by any one conservation advocate undermines the efforts and strategies of other conservation advocates. This increases expected aggregate net conservation losses.